Why visit America : stories - Baker, Matthew, 1985- (Henry Holt and Company, 2020)
"The citizens of Plainfield, Texas have had it with the broke-down United States. So they vote to secede, rename themselves America in memory of our former country, and happily set themselves up to receive tourists from their closest neighbor: America. Couldn't happen? Well, it might, and so it goes in the thirteen stories in Matthew Baker's brilliantly illuminating, incisive, and heartbreaking collection WHY VISIT AMERICA"--